The Southern Separatist Movement and the Civil War Years in Sudan, 1955-1972 - Abdullah Özdağ (Journal of Universal History Studies, 2024)
The diversity regarding the social construct of Sudan, co-ruled under Anglo-Egyptian Condominium, during the former half of 20th century led to remarkable crises with the administrative organisations commencing to be instituted during the process of transition into modern governmental structuring. The Southern Sudanese, unable to adapt to the Northern social construction prioritising Islam and Arabic culture regarding language, religion and traditions, claiming equal rights concerning newly organised institutions sparked civil unrest. Upon independence, Southerners struggled against the central government in an organized way to have more say on the future of their country. The dominant, sovereign and center-oriented policies of the Northerner leaders posed as the trigger underlying the Southerners being radicalized with their discourses incorporating initially autonomy, and later total independence. The 1960’s, when the independence effort of the nation was carried out via armed organisations systematically, not only eradicated the peaceful atmosphere, but also brought out hostility between the parties formidable to overcome. This study analyzes the representation issue (South-North Rivalry) regarding institutions during pre and post-independence periods and the political processes bringing forth the civil war.